THE PREDICTIVE POTENTIAL OF THE HUMOR FORMS AND STYLES FOR THE IMPLICIT PERSONALITY ASSESSMENT - Nosenko, Eleonora; Opykhailo, Olga (European Scientific Journal, ESJ, 2014)
Psychological studies of humor have been attracting the attention of personality researchers since long, but the recent focus on humor first as a transcendental character strength (Peterson & Seligman, 2004), and lately as an emotional one (Ruch et al., 2010) has opened up new prospects for investigating humor as a likely aspect of the implicit personality assessment. The objective of this study was to demonstrate that different forms and styles of humor manifestation can be indicative of both the level of virtuousness, the personality possesses, and the level of the emotional properties, attained by the individual in the course of personality development. Using the method of cluster analysis a sample of 125 participants was split into the opposite clusters (K-means algorithm) first on the variables of different humor styles and laughter-related categories in combination with the personality variables indicative of virtuousness, and then – in combination with a set of the emotional character strengths. Findings: the clusters opposite on the level of virtuousness appeared to differ significantly only on the adaptive (affiliative and self-enhancing) humor styles and gelotophobia, while the second clustering revealed differences in all the forms and styles of humor manifestation (including aggressive and self-defeating humor, gelotophobia, gelotophilia and katagelasticism). Taken the Dark Triad Trait variables as well as those of the psychological well-being were also controlled in the first clustering, the results suggest that humor can comprehensively predict individual differences.